Nursing diagnoses and adaptation problems among chronic renal patients - Farias de Queiroz Frazão, Cecília Maria; de Almeida Medeiros, Ana Beatriz; Paiva, Maria das Graças Mariano Nunes; Enders, Bertha Cruz; Oliveira Lopes, Marcos Venícios; Carvalho Lira, Ana Luisa Brandão (Investigación y Educación en Enfermería, 2015)
Objective. To identify similarities between NANDA International nursing diagnoses and Roy’s adaptation model among chronic renal patients undergoing hemodialysis. Methodology. Cross-sectional and descriptive study with 178 individuals selected, through consecutive convenience sampling, in a dialysis center located in the Northeast of Brazil. The study was conducted between October 2011 and February 2012. Data collection instruments included an interview form and a physical assessment. Results. Similarity was found between 20 nursing diagnoses and 22 adaptation problems. Roy’s adaptation modes that presented these relationships were: physiological, self-conception and role function. Conclusion. There are similarities between the two typologies. Furthermore, the use of the nursing process from the perspective of a theory inherent to the field supports care delivery and strengthens scientific knowledge in the profession. How to cite this article: Frazão CMFQ, Medeiros ABA, Paiva MGMN, Enders BC, Lopes MVO, Lira ALBC. Nursing diagnoses and adaptation problems among chronic renal patients. Invest Educ Enferm. 2015; 33(1):